2010
DOI: 10.1111/j.1872-034x.2010.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an oral branched chain amino acid‐enriched snack in cirrhotic patients with sleep disturbance

Abstract: Aim:  Sleep is closely related to physical and mental health. Sleep disturbance is reported in patients without encephalopathy. We examined the relationship among cirrhotic symptoms, laboratory data and sleep disturbances. Next, we examined the influence of a branched chain amino acid (BCAA) supplement on sleep disturbance in cirrhotic patients. Methods:  We investigated a total of 21 patients at Nagasaki University Hospital from January to June 2009. We constructed questionnaire items for the evaluation of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 37 publications
1
63
0
Order By: Relevance
“…In this context, CSS is calculated using items from a cirrhosis symptom questionnaire that was developed in our previous study, and three of the 12 items in this tool are associated with sleep disturbances. Moreover, our previous study reported that CSS, excluding the scores for the three sleep disturbance-related items, is associated with liver damage (18). In the present study, three CSS items (hand tremors, appetite loss and decreased strength) were significantly associated with MHE, and these associations validate the previously reported associations between MHE and the following responses: 'I do not maintain balance', 'I act irritable or impatient with myself', 'I am not doing any of my usual physical recreations or activity' and 'I am eating much less than usual' (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, CSS is calculated using items from a cirrhosis symptom questionnaire that was developed in our previous study, and three of the 12 items in this tool are associated with sleep disturbances. Moreover, our previous study reported that CSS, excluding the scores for the three sleep disturbance-related items, is associated with liver damage (18). In the present study, three CSS items (hand tremors, appetite loss and decreased strength) were significantly associated with MHE, and these associations validate the previously reported associations between MHE and the following responses: 'I do not maintain balance', 'I act irritable or impatient with myself', 'I am not doing any of my usual physical recreations or activity' and 'I am eating much less than usual' (25).…”
Section: Discussionmentioning
confidence: 99%
“…An 'impact factor' for each item was calculated, which was defined as the product of the frequency of the item and the mean importance that the patients attributed to the item. The impact factor for each item ranged from 0 to 3, and the CSS was calculated as the sum of the impact factors (18). The Epworth Sleepiness Scale (ESS) (21) was used to evaluate daytime hypersomnolence; ESS scores range from 0 to 24, and a score of ≥10 indicates significant daytime hypersomnolence.…”
Section: Diagnosis Of Mhementioning
confidence: 99%
See 2 more Smart Citations
“…The restless legs syndrome (RLS) is a common complication of cirrhosis and affects sleep status as evaluated by the Pittsburg sleep quality index (PSQI), and QOL is evaluated by the SF‐36 . The Epworth sleepiness scale (ESS) in patients with cirrhosis can be improved by ingestion of branched chain amino acid supplements . Previously, we used these PROs and could evaluate changes in symptoms in response to liver transplantation and supplementation …”
Section: Introductionmentioning
confidence: 99%